2013
DOI: 10.1371/journal.pone.0058018
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Potential of Prepubertal Mouse Oocytes Is Compromised Due Mainly to Their Impaired Synthesis of Glutathione

Abstract: Although oocytes from prepubertal animals are found less competent than oocytes from adults, the underlying mechanisms are poorly understood. Using the mouse oocyte model, this paper has tested the hypothesis that the developmental potential of prepubertal oocytes is compromised due mainly to their impaired potential for glutathione synthesis. Oocytes from prepubertal and adult mice, primed with or without eCG, were matured in vitro and assessed for glutathione synthesis potential, oxidative stress, Ca2+ reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 61 publications
2
43
0
1
Order By: Relevance
“…In this study, using bovine SCNT embryos as the model, we systematically assessed effects of culture medium renewal on blastocyst formation and quality ( in vitro development) and following growth to term ( in vivo development). Our results (Table 3) showed that compared with routine renewal treatment, continuous nonrenewal culture system exhibited a significant improvement in blastocyst formation, total cell number, ratio of ICM/TE (Fig 5), pregnancy and calving (Table 4), as well as a remarkable decrease in cellular stress (reduced expression of Bip , an endoplasmic reticulum stress marker [33], Fig 6) and apoptosis (increased Bcl-2— an anti-apoptosis marker [34] and reduced Bax— a pro-apoptosis marker [35], Fig 6; and less TUNEL signal, Fig 4). Notably, coupling of endoplasmic reticulum stress and apoptosis detected in our study is consistent with previous studies [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, using bovine SCNT embryos as the model, we systematically assessed effects of culture medium renewal on blastocyst formation and quality ( in vitro development) and following growth to term ( in vivo development). Our results (Table 3) showed that compared with routine renewal treatment, continuous nonrenewal culture system exhibited a significant improvement in blastocyst formation, total cell number, ratio of ICM/TE (Fig 5), pregnancy and calving (Table 4), as well as a remarkable decrease in cellular stress (reduced expression of Bip , an endoplasmic reticulum stress marker [33], Fig 6) and apoptosis (increased Bcl-2— an anti-apoptosis marker [34] and reduced Bax— a pro-apoptosis marker [35], Fig 6; and less TUNEL signal, Fig 4). Notably, coupling of endoplasmic reticulum stress and apoptosis detected in our study is consistent with previous studies [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of GSTO1 increased in both the first and second age transition. Although there is no study of GSTO1 in mammalian oocytes, impaired synthesis of glutathione is indicted as the main cause for compromised developmental potential of pubertal mouse oocytes in mice (Jiao et al 2013); hence, the increased abundance of GSTO1 in old oocytes may facilitate development. Abundance of the cell death inducer BAX was high in pubertal oocytes and decreased in the first age transition.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicated that granulosa cells apoptosis can cause the follicular atresia [2]. Moreover, several studies showed that follicular granulosa cells have a crucial role in oocyte potency in sheep [3], mouse [4], porcine [5], goat [6]and rat [7]. Therefore, follicular granulosa cells play an important function during female reproduction.…”
Section: Introductionmentioning
confidence: 99%